Perilaku Penggunaan Masker pada Pasien TB Paru - Yulia Susanti; Muhammad Khabib Burhanudin Iqomh; Fendi Wicaksono (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2020)
Pulmonary TB is an air-borne disease. Pulmonary TB transmission to someone through phlegm in the form of droplets that spread into the air. One of the prevention of transmission of pulmonary TB is the use of masks. Good behavior in pulmonary TB patients is required to wear respiratory protection when leaving the house and when in direct contact with people because the mask can filter out submicron-sized particles. Respiratory protection if not used for pulmonary TB patients in contact with people, it will increase the risk of transmitting the disease. This study aims to determine the behavior of the use of masks for pulmonary TB patients in Dr. H. Soewondo Kendal. This research is a non-hypothesis descriptive study with cross sectional approach, a sample of 78 respondents with accidental sampling technique. The results of this study indicate that the characteristics of respondents based on the average age of 44.63 years with an age range of 17-78 years, the majority of male sex 43 (55.1%) respondents, educated high school 31 (39.7%) respondents , has a job as a laborer 15 (19.2%) of respondents, low income of 45 (57.7%) respondents, average length of illness for 6.69 months with a range of 1-60 months. The behavior of using masks in the majority of pulmonary TB patients is good as many as 64 (82.1%) respondents and the behavior of using masks is not good as many as 14 (17.9%) respondents. One's actions in carrying out health activities, especially in the use of masks, are in addition to being influenced by knowledge and attitudes. There are several factors that influence it, including the physical environment and the socio-cultural environment. Someone who has good knowledge and attitude can still be at risk of taking unfavorable health measures because of the influence of the surrounding environment, habits and activities of people with pulmonary TB.